Assessment of Knowledge towards Tuberculosis among general population in North East Libya - Mukhtar A. Sollimana, Mohamed Azmi Hassalia, Mahmoud Al-Haddada, Mukhtar M. Hadida, Fahad Saleema, Muhammad Atifa & b,Hisham Aljadheyc (Journal of Applied Pharmaceutical Science)
The study aimed to evaluate the level of Tuberculosis (TB) related knowledge among general public in North East Libya. A cross sectional study was undertaken in 2009. A prevalidated questionnaire consisting of 23 items was sent to 1500 residents among five cities in North East Libya. In addition to the demographic details, the survey instrument was designed to collect information relating to transmission, diagnosis, risk factors, treatment and prevention of TB. Descriptive analysis was used to elaborate demographic information. Inferential statistics (Chi-square test and one-way ANOVA) were used whenever appropriate. P value of less than 0.05 was considered as significant. All data was analyzed using SPSS version 16.0. The overall knowledge towards TB among general population was measured as low. Mean knowledge score was 11.4±3.9 which was significantly higher among Libyans (11.7±3.8) than non Libyans (9.7±4.7, t=26.13) (P
Keywords: As Tuberculosis, assessment, knowledge, North East Libya